2014
DOI: 10.1080/07315724.2013.866527
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Precautionary Principle to Nutrition and Cancer

Abstract: By adopting the precautionary principle for nutrition research, this review aims to serve as a useful tool for practitioners and patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 69 publications
0
28
0
Order By: Relevance
“…To this point, a review published in 2014 identified eating soy during childhood/adolescence as 1 of 6 steps to reducing cancer risk [83]. Also, a recent commentary in the ‘American Journal of Epidemiology' concluded that ‘… growing evidence … links childhood and adolescent lifestyle and environmental exposures with subsequent risk of cancers arising in adulthood' [57].…”
Section: Discussionmentioning
confidence: 99%
“…To this point, a review published in 2014 identified eating soy during childhood/adolescence as 1 of 6 steps to reducing cancer risk [83]. Also, a recent commentary in the ‘American Journal of Epidemiology' concluded that ‘… growing evidence … links childhood and adolescent lifestyle and environmental exposures with subsequent risk of cancers arising in adulthood' [57].…”
Section: Discussionmentioning
confidence: 99%
“…42 Soy products high in isoflavones, such as edamame, tofu, tempeh and miso soup, have been found to have anticarcinogenic effects in preclinical studies, having been associated with apoptosis, antiangiogenesis and reduced sex hormone levels. 41 One study found that supplementation with 200 mg of soy isoflavones daily over two to six weeks before breast cancer surgery showed a nonsignificant trend toward inhibition of cancer growth compared with a control group. 43 A meta-analysis of five prospective cohort studies from the United States and China found that high consumption of soy protein or soy isoflavones after breast cancer diagnosis was associated with a 26% decrease in recurrence (HR 0.74, 95% CI 0.61-0.85) and a 16% reduction in breast cancer mortality (HR 0.84, 95% CI 0.71-0.99) compared with low consumption.…”
Section: Soymentioning
confidence: 99%
“…4,35 • Dietary saturated fat, especially from high-fat dairy products, may be associated with increased breast cancer mortality. 3,32,33 • Soy products have not been found to increase breast cancer recurrence 41 and may actually reduce it.…”
Section: Dietmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with increasing rates of animal product consumption come increased rates of many "diseases of nutritional extravagance" (Shu et al, 1993, Campbell et al, 1998, Gonzales et al, 2014 such as heart disease, type 2 diabetes, and many cancers. In fact, the leading cause of human death in the world is heart disease, killing approximately 8.5 million people annually and comprising approximately 15% of all deaths.…”
Section: Human Health Connectionmentioning
confidence: 99%